Effect of post-harvest distribution environment on quality deterioration of mango fruits - Yasunaga,E. (International Society for Horticultural Science, 2015)
This study aimed to determine the effects of the post-harvest distribution environment of the fruit of mango (Mangifera indica L.) imported from Thailand to Japan and on physiological changes in stored fruit. Mango fruits of 'Namdok Mai', 'Maha Chanok', and 'Chok Anan' were harvested from orchards at Phrao, Lampang, and Mae Jo, Thailand, respectively. The distribution environment (temperature, relative humidity, and vibration conditions during transport) of fruit imported from Phrao, Thailand to Fukuoka, Japan was measured with a gravity shock recorder. Immediately after harvest and immediately after distribution fruit were stored for 6 days at 15, 25 and 35°C. The contents of L-ascorbic acid (L-AsA), sucrose, glucose and fructose, and total soluble solids, and hardness score and respiration rate were measured as indices of the deterioration in fruit quality. CO2 evolution rate and O2 consumption rate of fruit after distribution were measured in storage chambers at 15, 25 and 35°C ventilated with air at a flow rate 100 ml min-1. L-AsA content at harvest was about 42 mg 100 g FW-1 at Phrao and at Mae Jo, and about 30 mg 100 g FW-1 at Lampang. L-AsA content of fruit after distribution was about 50% of that measured at harvest. Both CO2 evolution rate and O2 consumption rate of fruit increased with increasing temperature.